Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1124/jpet.301.1.293
|View full text |Cite
|
Sign up to set email alerts
|

Human Organic Anion Transporters and Human Organic Cation Transporters Mediate Renal Transport of Prostaglandins

Abstract: Prostaglandin E 2 (PGE 2 ) and prostaglandin F 2␣ (PGF 2␣ ) have been used for the induction of labor and the termination of pregnancy. Renal excretion is shown to be an important pathway for the elimination of PGE 2 and PGF 2␣ . The purpose of this study was to elucidate the molecular mechanism of renal PGE 2 and PGF 2␣ transport using cells stably expressing human organic anion transporter (hOAT) 1, hOAT2, hOAT3, and hOAT4, and human organic cation transporter (hOCT) 1 and hOCT2. A time-and dose-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
108
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(114 citation statements)
references
References 33 publications
(47 reference statements)
5
108
0
1
Order By: Relevance
“…Thus, the expected concentration of free PGE 2 is likely to be in a range that suffices to generate an effect on OAT1 and OAT3. PGE 2 is a substrate for both OAT mentioned (14). With respect to a role of peripheral PGE 2 in fever (as suggested by Ivanov et al [19]), it would make sense that renal clearance is impaired together with metabolic clearance to achieve high plasma levels of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the expected concentration of free PGE 2 is likely to be in a range that suffices to generate an effect on OAT1 and OAT3. PGE 2 is a substrate for both OAT mentioned (14). With respect to a role of peripheral PGE 2 in fever (as suggested by Ivanov et al [19]), it would make sense that renal clearance is impaired together with metabolic clearance to achieve high plasma levels of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of protein binding, proximal tubular secretion of PGE 2 plays a major role in renal excretion (22). Because PGE 2 is a substrate for both OAT1 and OAT3 (14), these transporters represent the rate-limiting basolateral uptake step of proximal tubule PGE 2 secretion. Therefore, it seems reasonable to speculate that renal secretion of PGE 2 also could be impaired in the above-mentioned fever model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 For sodium-independent uptake, organic anion-transporting polypeptides (OATPs) of the SLC21 (SLC0) family, such as OATP-B, 7,8 OATP-C, [9][10][11] and OATP8, 12,13 mediate the transport of a variety of organic anions such as sulfobromophthalein, bile salts, and sulfate-conjugated steroid hormones, although their driving forces are still unclear. In addition, organic anion transporter 2 (OAT2) in the SLC22 family mediates the transport of organic anion such as para-aminohippurate, 14 prostaglandins, 15 zidovudine, 16 tetracycline, 17 and salicylates 18 in a sodium-independent manner. Recently, Kobayashi et al 19 have reported that it also mediates the transport of steroid sulfates as well as several drugs.…”
mentioning
confidence: 99%
“…From transgenic mice harboring the simian virus 40 large Tantigen gene, S2-hOAT1, S2-hOAT2, S2-hOAT3, and S2-hOAT4 were established and characterized as previously reported Hosoyamada et al, 1996;Takeda et al, 2002;Kimura et al, 2002). Briefly, the full-length cDNAs of hOATs were sub-cloned into pcDNA 3.1 (Invitrogen), a mammalian expression vector.…”
Section: Organic Anion Transporter (Oat) In Vitro Studiesmentioning
confidence: 99%